Investigation of WLS state estimation convergence under topology errors and load increment. (1st January 2013) - Chen, Jiaxiong; Liao, Yuan
State estimation plays an essential role in real-time power system monitoring, control, and automation. Utilising non-linear optimisation theory, it determines the optimal system states based on the network model and the gathered measurements from the system. Conventional weighted least square (WLS) state estimation algorithm may suffer divergence problem due to the occurrence of topology error. This paper studies the impact of the topology errors on the convergence property of WLS state estimation under load increment. Two types of load increment are utilised: one is the load increment of all load buses, and the other is a single load increment. The IEEE 118-bus system is used as the test case and simulation results are reported. In addition, phasor measurement unit (PMU) measurements including voltage magnitude and angle measurements are added to the measurement vector of state estimation to verify if they could solve the divergence problem and improve state estimation accuracy.